RELATIONSHIP BETWEEN HIGH-SENSITIVITY C-REACTIVE PROTEIN (HS-CRP) SERUM LEVELS AND THE NUMBER OF CORONARY ARTERY LESION IN ACUTE CORONARY SYNDROME (ACS) PATIENTs - Nova Sipahutar, Rahmad Isnanta, & Refli Hasan (International Journal of Research Science and Management, 2019)
Introduction: Acute Coronary Syndrome (ACS) is one of the clinical manifestations of Coronary Heart Disease (CHD) that has high morbidity and mortality. Atherosclerosis is a process that underlies the occurrence of CHD. Inflammation plays an important role in the process of atherosclerosis. Some prospective studies suggest that inflammatory markers such as a high sensitivity C-Reactive Protein (hs-CRP) serum is a predictors of cardiovascular events. Aim: The aim of this study was to determine the relationship of hs-CRP levels with the number of coronary artery lesions in patients with Acute Coronary Syndrome (ACS). Methods: This cross-sectional study was conducted at the H. Adam Malik General Hospital in Medan from October to December 2018 to 48 ACS patients. Examination of hs-CRP levels, laboratory analysis for blood and coronary angiography was made in this study. Hs-CRP levels were divided into 2 groups based on the risk of cardiovascular events. The number of coronary artery lesions was assessed by vessel score. Furthermore, association of serum hs-CRP with vessel scores compared using Chi-Square analysis. Results: From 48 research subjects, there were 16 (33.33%) people each with STEMI, NSTEMI and UAP respectively. Subjects in the group with hs-CRP≥3 mg / L as many as 15 (31.25%) people and the group with hsCRP<3 mg / L were 33 (68.75%) people, while based on vessel scores, subjects with a Vessel score of 0, 1, 2, and 3 were as many as 10 (20.83%), 12 (25.00%), 10 (20.83%), and 16 (33.33%) people respectively. The mean hsCRP level in patients with Vessel scores 0 was 0.510 ± 0.203 mg / L, 1 was 1.967 ± 0.729 mg / L, 2 was 2.010 ± 0.689 mg / L, and 3 was 5.388 ± 1.979 mg / L. In the Chi-Square analysis, there was a significant relationship between hs-CRP levels and vessel score (p <0.001). Conclusion: There was a significant relationship between hs-CRP levels and the number of coronary artery lesions in ACS patients.